Effect of salinity stress on foliar fungal diseases of groundnut - I.K. GIRDHAR, R.D. PADAVI and P.K. BHALODIA, VINOD KUMAR*, M. P. GHEWANDE, (Indian Phytopathology, 2010)
The effect of soil and irrigation water salinity on severity of major foliar fungal diseases of groundnut viz., early leaf spot (Cercospora arachidicola), late leaf spot (Phaeoisariopsis personata) and rust (Puccinia arachidis) was investigatedduring rainy season of 2003 and 2004 in black clay calcareous soil. The salinity in the experimental plots was developed as aresult of saline water irrigation over the years. Four levels of saline irrigation water viz., 0.5 (control), 2.0, 4.0 and 6.0 dS m-1 and five cultivars were tested in a split plot design. The results revealed that with increase in salinity stress the severity of major foliar fungal diseases decreased. At higher salinity the crop growth was severely affected and there was no corresponding increase in pod yield of the crop even though the disease was low. Based on the studies it is concluded that although groundnut is a sodium sensitive crop, it can be grown profitably up to a threshold salinity stress of 2.0 dS m-1 irrigation water salinity (ECiw) and 2.5 dS m-1 soil salinity in black clayey soil as at this salinity the severity of foliar diseases were less and the pod yield was maximum.